ANALISIS PENDAPATAN MASYARAKAT MELAYU DI DESA PEKANTUA KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Yogi Hiro; Evy Maharani; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Malay community in Pekantua Village still predominate that is 80%. geographically Pekantua Village resid in alongside river stream of Indragiri, Pekantua Village is one of the oldest village in Indragiri Hilir. The purpose of this research is to determine the income level of Malay community in Pekantua Village Kempas District Indragiri Hilir Regency. This research conducted by purposive sampling of 30 Malay community samples. The result showed that the income level of Malay community in Pekantua Village consists of father income, mother income, and child income. Father income who above regency minimum pay (UMK) Indragiri Hilir Regency going into effect in the year 2015 is Rp. 1.940.500,-  as many as 19 respondents from 30 respondents (53,33%), who have income under regency minimum pay (UMK) as many as 11 respondents (36,66%). The main livelihood of father is rubber farmer, and secondary livelihood are ship worker, fishermen, trader, builder, and sand miner. Mother income who above regency minimum pay (UMK) as many as 2 respondents from 30 respondents (6,67%), who have income under regency minimum pay (UMK) as many as 12 respondents (40,00%). The livelihood of mother is farmer and trader. Child income who above regency minimum pay (UMK) as many as 1 respondents from 30 respondents (3.33%), who have income under regency minimum pay (UMK) as many as 6 respondents (20,00%), and who have not income as many as 23 respondents (76,66%). The livelihood of child is farmer, ship worker, trader.     Key words: Malay community, income, farmer